(untitled) (The Research of Medical Science Review, 2025)
Orthopedic surgical site infections (SSIs) are common and can lead to increased morbidity, extended hospital stays, and higher costs. Despite advancements in surgical techniques, SSIs persist, underscoring the need for improved infection prevention. For closed fractures, including Open Reduction and Internal Fixation (ORIF), best practices recommend limiting antibiotic prophylaxis to 24 hours post-surgery to reduce the risk of SSIs and antibiotic resistance. This study aimed to explore the impact of antibiotics on surgical site infections in closed fracture patients undergoing open reduction and internal fixation. This cross-sectional study at Gulab Devi Teaching Hospital focused on patients with closed fractures treated with open reduction and internal fixation. Data were collected through convenient sampling and a revised questionnaire. Qualitative variables were analyzed using percentages and frequencies, while means and standard deviations were used for quantitative variables. Data analysis was performed using SPSS software. This study identified both significant and non-significant effects of various independent variables. Diabetes mellitus was significantly associated with wound infections (p=0.039), and body mass index was a strong predictor of complications (p=0.001). The culture report suggested a significant link between bacterial type and infection risk (p=0.000). However, no significant associations were found for implant type (0.514), fracture site (p=0.580), or preoperative antibiotics (p=0.482). Ceftriaxone and cefazoline antibiotics reduced post-surgery infection rates by 1.9%, with chronic illness, diabetes, hypertension, and BMI influencing infection odds.